Analisis Kualitas Susu pasteurisasi Akibat Penyimpanan Dalam Refrigerator - Helmi M. Yahya (Jurnal Agripet, 2001)
ABSTRACT. The research was done at Animal Product Technology Laboratory, Agriculture Faculty, Syiah Kuala University from July, 1998. This aimed of the research to know Influence of store in refrigerator to quality of milk pasteurization. The result showed that there were significant (P0.05) to composition of lipid and dry matter of milk pasteurization after 96 hours stoored in refrigerator. Whereas to protein content indicated do not different (P0.05).